Increasing Costs For Development of Air Force Plane on The Financial Stability of Bank Indonesia (BI) In The Defense Budget - Khaerudin; Santosa, Anton Iman; Kustiawan, Bambang; Muna, Arifa F.Z. (Dinasti Publisher, 2024)
The Indonesian Air Force is directed to increase the fleet of fighter aircraft and radar units to meet Indonesia's air defense needs. Fulfilling air defense needs, especially the construction of Indonesian Air Force aircraft, requires a budget allocation from the government. Policies regarding budget allocations and their implementation certainly require more complex policies. Therefore, it is necessary to map and identify the Increased Cost of Aircraft Development for the Indonesian Air Force on the Financial Stability of Bank Indonesia (BI) in the Defense Budget. This type of research is qualitative with the method of observation, interviews and document studies. Data analysis was carried out interactively descriptive until saturated using the trangulation method. The results of the study indicate that the source of the TNI AU's defense budget comes from the APBN which is sourced from GDP, grants and foreign loans. The dynamics of increasing the defense budget in the procurement of TNI-AU aircraft depend on the dynamics of threats, availability of resources and government policies. The projected increase in the Indonesian Air Force's defense budget tends to fluctuate with an average budget change in 2018-2021 of 42%. The procurement of Indonesian Air Force aircraft is also projected to increase as a way to maintain the sovereignty of the Republic of Indonesia in accordance with the dynamics of the strategic environment. The defense budget affects and is influenced by the financial stability of Bank Indonesia, particularly the APBN, GDP and economic growth.